Pengaruh Konseling Individual Menggunakan Teknik Behavioral Terhadap Perilaku Agresif Pada Remaja di Lingkungan Sosial - Isak Iskandar; Hailala Najwa Isba (Jurnal Riset Multidisiplin Edukasi, 2025)
Aggressive behavior in adolescents is a form of psychosocial problem that can hinder personality development, social interaction, and academic achievement. This study aims to determine the effect of individual counseling using behavioral techniques on aggressive behavior in adolescents in the social environment. This study used a quantitative approach with a one group pretest-posttest design. The research sample consisted of 15 adolescents who were identified as having moderate to high aggressive behavior. Data were collected through an aggressive behavior questionnaire and analyzed using a paired sample t-test statistical test. Individual counseling services were provided for six sessions, using behavioral techniques such as positive reinforcement, modeling, and self-monitoring. The results of the data analysis showed that there was a significant decrease in aggressive behavior scores between the pretest and posttest. The average pretest score of 73.3 decreased to 55.4 in the posttest, with a significance value of 0.003 (p <0.05). These findings indicate that individual counseling based on behavioral techniques is effective in helping adolescents manage and change their aggressive behavior in a more positive direction. This study provides practical implications for BK teachers, parents, and educational institutions in dealing with adolescent deviant behavior through structured interventions. The behavioral approach has proven to be applicable, efficient, and relevant for use in counseling settings in schools and communities.